Trust me, I have a PhD: the effects of religion, political conservatism, and exposure to science feature stories on trust in science - Quesnell, Bethany (Kansas State University, 2015)
Widespread debates about scientific issues, from global warming to vaccinations, have raised questions about public trust in science and scientists. Many studies have attempted to determine the cause of observed declines in public trust. This project employs framing theory, suggesting that the way science frames research might improve public trust. Research questions explore whether political conservatism, public religiosity, and exposure to a feature story about a scientist affects trust in science and scientists. A between-subjects quasi-experiment exposed participants to feature articles about scientists in either controversial or non-controversial fields, and asked a series of questions in order to measure the participant’s trust in science and scientists. Results indicated that participants who were male or participants who had some college education and who read the non-controversial feature story were statistically more likely to have a higher level of trust in science and scientists than any other group. Suggestions for future studies are discussed.
Keywords: Scientific communication; Trust in science; Political conservatism; Public religiosity; Politicized/controversial science; Mass Communications (0708)